Compact Size UWB Monopole Antenna with Triple Band-Notches - W. Ali; A. A. Ibrahim; J. Machac (Radioengineering, 2017)
This paper presents triple band notched ultra wide band (UWB) monopole antenna with overall size of 36 × 32 mm2 fed by microstrip transmission line. In order to achieve a good impedance matching from 2.7 GHz to 13.4 GHz, a tapered transition between the rectangular patch and the feeding line is utilized. The three notched frequency bands are accomplished by a defected microstrip structure (DMS) which is inserted in the microstrip feeding line and by an open loop slot etched in the radiating patch. The three band notches are 3.15-4 GHz, 5.7-6.3 GHz and 7.9-8.6 GHz. They prevent the receiving of the signals of IEEE 802.16 WiMAX band, WLAN band, and ITU applications respectively. The UWB antenna was designed and simulated then fabricated and tested in order to investigate its impedance and radiation characteristics. Good agreement between the simulated and measured data is achieved. The obtained results show that the proposed antenna is convenient for UWB applications.